FISHERIES LOGISTICS PERFORMANCE IMPROVEMENT STRATEGY AT MALUKU SEA TOLL NETWORK PORTS: HIERARCHICAL CONCEPTION OF DMAIC LOGISTICS MODEL - Arif, Hadi Sholekhan; Mustaruddin; Lembito, Hoetomo; Puspito, Gondo (Departemen PSP IPB, 2025)
Indonesian government is developing a sea toll program to facilitate logistics services for essential goods and basic goods, especially in the Eastern Indonesia Region. One of the essential goods and important logistics services in the region is fish logistics services, some of which have transit ports in Maluku Province. However, its utilization had not been optimal, because fish logistics activities were still mediocre and its services were inferior to other essential and basic goods. This study aimed to determine a strategy to improve fish logistics performance at ports in the Maluku sea toll network. The research locations are the Ambon Nusantara Fisheries Port and the Dobo Coastal Fisheries Port. The method used in the study is the analytical hierarchy process (AHP) which is a hierarchical stage of DMAIC modeling. Research results showed that the strategy of integrating efficient fish logistics and sea toll systems, so that logistics costs (storage, transportation) are low, and are able to overcome excess supply and excess demand in the surrounding area (STG-2) was a priority strategy to support improving the performance of fish logistics at the ports of the Maluku sea toll network. The results of the consistency ratio calculation also obtained a CR value of 0.0024 (consistent), and the strategy was also stable against changes in the required criteria conditions. Key words: archipelagic waters, DMAIC model, fisheries, port industry, staple goods